Kristine M. Alpi, AHIP, FMLA, Medical Library Association President, 2021–2022 - Patricia E. Gallagher (University Library System, University of Pittsburgh, 2021)
In this profile, Kristine M. Alpi, AHIP, FMLA, Medical Library Association (MLA) president, 2021–2022, is described as committed to public health, professional development, and the growth and evolution of MLA. She teaches and speaks on the shared health impact from interactions among animals, humans, and the environment, and she mentors graduate students and fellows in librarianship and informatics. Alpi earned her PhD in educational research and policy analysis in 2018 and directs the Oregon Health & Science University Library.